Online survey of visitation and tourist behaviour in a protected territory—the case of Urdini Lakes, Rila National Park - Siya Cholakova; Elka Dogramadjieva (Journal of the Bulgarian Geographical Society, 2023)
The lack of comprehensive and reliable data regarding visitation and tourist behaviour at local level and especially in vulnerable environment has been acknowledged long ago as an issue by both academics and practitioners. In Bulgaria, this type of data is scarce and inconsistent, regardless of the increased visitor flow in certain mountain areas. The mass adoption of social media, as well as the development of online travel communities, allow research with more ease the target population, as opposed to traditional resource-intensive monitoring methods. This paper presents the results of an online survey of visitors to Urdini Lakes in Rila National Park, Bulgaria. The aim of the study is to identify the overall recognition of the area and the extent of effective visit by mountaineers, as well as the profile of visitors and their behaviour. According to the results of this study, the influence of social media on visitation and tourist behaviour in the case of Urdini Lakes appeared lower than expected and much outweighed by factors like accessibility and trail difficulty. Further research should combine more innovative and mixed methodologies regarding the usage of social media and its influence, which can combine and compare different types of data such as surveys, geolocated big data and visual methods.